Regression Analysis of CAR, NPL-Net, LDR on Increasing Return on Asset (Case Study on Banking Companies Listed on IDX in 2018-2020) - Mohammad Hamim Zajuli Al Faroby (Internasional Journal of Data Science, Engineering, and Anaylitics, 2022)
Banking is a financial institution tasked with collecting funds from the public and then channeling them back to obtain income. The bank's performance can be seen by comparing the ratio figures in the annual financial statements that the bank has achieved. Therefore, this study aims to determine the CAR, NPL-Net, and LDR, which affect bank profitability or Return on Assets. This research method uses Multiple Linear Regression Analysis with secondary data and a ratio measurement scale, and the number of samples is 90 samples from 30 banking companies during the 2018-2020 period. This data is sourced from the Indonesia Stock Exchange, with the Judgment Sampling technique. The sample was reduced to 84 by the outlier test due to abnormal data. Based on the results of the analysis, it is known that CAR and LDR have no significant effect on Return on Assets, otherwise, NPL-Net has a significant effect on Return on Assets, and CAR, NPL-Net, LDR simultaneously have a significant effect on Return on Assets.